Features of the immobilization of nanosilver on an activated carbon fiber nanostructural matrix for the development of antibacterial materials for medical use - Kononko, I.V.; Klipov, V.D.; Boshytska, N.V.; Protsenko, L.S.; Kononko, N.V. (Reports of the National Academy of Sciences of Ukraine, 2019)
The study of the processes of immobilization of silver nanoparticles upon the activated carbon fiber nanostructural matrix (ACFNM) of different volumetric capacities — 0.344; 0.5—0.6, and 1.0 cm3/g, carried out by the liquid-phase and gas-phase methods is performed. It is shown that the nature of the reducing agent affects the shape and distribution of silver agglomerates on ACFNM samples. Comparing the effect of sodium citrate and tannin, it is concluded that, in the case of tannin, a larger number of silver nanoparticals and their agglomerates on the surface of ACFNM is deposited. It is established that, after the immobilization of silver on ACFNM samples of different volumetric capacities, a significant sorption potential of the carbon matrix remains. This will give the opportunity for ACFNM to ensure the absorption and neutralization of pathogenic microorganisms, when used in medicine.